Structural Characterization and Antimicrobial Activity of Cocculus hirsutus L. Leaf Extract by Liquid Chromatography-mass Spectroscopy: Structural Characterization and Antimicrobial Activity of Cocculus hirsutus L. Leaf Extract by Liquid Chromatography-mass Spectroscopy - Ranganayakulu, G. S. (International Journal of Pharmaceutical & Biological Archive, 2018)
Many number of the plant species including Cocculus hirsutus L. is being used as the sources of herbal medicine. Present work was mainly focused with the identification of the therapeutic properties of C. hirsutus L. leaf extracts. The leaf extracts of methanol, aqueous, chloroform, and benzene showed solvent dependent qualitative and quantitative phytochemical presence as well as antimicrobial activity. Whereas the leaf extracts of methanol and chloroform showed significantly high antimicrobial activity than water and benzene extracts. Further methanol leaf extract of C. hirsutus performed to liquid chromato y-mass spectroscopy (LC-MS) for identification of active antimicrobial compound structure. LC-MS studies give 26 structural compounds. Docking (annotating) studies revealed that among 26 compounds the Compound-5 (Hexadecanoic acid - (1R, 2R, 3S, 4R, 6S)-4, 6-diamino-2, 3-dihydroxy cyclohexyl 2,6-diamino-2,6-dideoxy-Î±-D-glucopyranoside) showed highest docking fitness score with the bacterial membrane protein sortase-A. Our data suggest that methanol extract of C. hirsutus leaf possess medicinally significant antimicrobial compounds and thus justify the use of this leaf as folklore medicine for preventing human microbial related diseases.